Longitudinal study to assess the prevalence of hypogonadism in HIV-infected South African men and its association with bone density, body composition, metabolic abnormalities (dysglycaemia, dyslipidaemia) and quality of life. - van Der Merwe, Le Roux (Division of Endocrinology and Diabetology, 2022)
Background: Hypogonadism has been described in association with HIV infection and anti-retroviral therapy (ART). Furthermore, hypogonadism is associated with comorbidity and a reduced quality of life. The prevalence of hypogonadism in HIVinfected South African men is unknown. We examined the prevalence of hypogonadism in HIV-infected men before and 12 months after the initiation of ART. Methods: This is a sub-study of the McHAART Study designed to investigate the metabolic complications of ART. HIV-infected men attending the Crossroad Community Healthcare Clinic were conveniently sampled prior to commencing ART and then followed for 6-months, 12-months and 24-months. Here we report on total testosterone, LH, FSH, SHBG and free testosterone measured on blood samples taken at 08h00 prior to initiating ART (baseline) and then again at 12 months on ART. Results: There were 44 patients at baseline and 30 patients at the 12-month visit. There were no participants with hypogonadism at baseline or after 12 months on ART. Testosterone levels or change in testosterone levels were not associated with alcohol intake, bone miner density, body mass index, waist circumference, fasting glucose, HOMA IR, HOMA β, fasting cholesterol or blood pressure at baseline or 12 months. Conclusions: There were no cases of hypogonadism in HIV-infected ART-naïve men and there were no cases of hypogonadism in HIV-infected men on ART for 12 months in this study population. Testosterone levels or change in testosterone levels were not associated with any measures of body composition, glucose metabolism, lipids or bone mineral density.